MAPPING THE MARGINS: A SOCIO-CULTURAL STUDY OF TISTAPARER BRITANTO - Choudhury, Barunjyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
We aim to reinterpret old Bengali narrative literature through the lens of modern novelistic experiences, much like Mikhail Bakhtin delved into ancient European carnival literature, Greek comedy, Menippean satire, and Christian confessional writings to analyze Dostoevsky’s novels. Without modern novelistic aesthetics, it would have been impossible to uncover the narrative lineage from ancient and medieval literature to contemporary times. Bakhtin’s exploration of the past was intended to expand the aesthetic scope of the modern novel and to define its unique features. Similarly, we must also approach Bengali's old narrative literature using the aesthetic principles of the modern novel.